MANAJEMEN PENDIDIKAN ANAK USIA DINI BERBASIS PEMBELAJARAN BERPUSAT PADA ANAK: PERSPEKTIF NATURALISME ROMANTIK - SYAMSURIADI Syamsuriadi (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2018)
Abstract. The management of early childhood education based on child-centered learning is a learning strategy that orients all management functions like planning, organizing, and evaluating to accelerate the children creativity during the learning process. Keywords:The early childhood education is unique process. Hence, romantic-naturalism is a paradigm that can support the effort.